LEGAL BASIS OF THE PRINCIPLES OF CRIME PREVENTION IN THE LEGISLATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the main principles and their legal foundations established in the legislation of the Republic of Uzbekistan in the field of crime prevention. The principles reflected in the laws, state programs, presidential decrees and resolutions, as well as relevant sectoral documents regulating crime prevention activities are analyzed based on such criteria as legality, systematicity, humanity, interest and effectiveness. At the same time, the implementation of these principles in practice and development trends are also considered.